A comprehensive review on ethnomedicine, phytochemistry, pharmacology, and toxicity of Tephrosia purpurea (L.) Pers. (8th March 2020) - Rao, A. S.; Yadav, S. S.; Singh, Priya; Nandal, Abhishek; Singh, Neetu; Ganaie, S. A.; Yadav, Neelam; Kumar, Rajesh; Bhandoria, M. S.; Bansal, Pradeep
Abstract : Tephrosia purpurea (L.) Pers. is a well‐known plant in Ayurveda and named " Sarwa wranvishapaka " for its property to heal wounds. Traditionally, it is practiced for impotency, asthma, dyspepsia, hemorrhoids, syphilis gonorrhea, rheumatism, enlargement of kidney and spleen. It is an important component of herbal preparations like Tephroli and Yakrifti used to cure liver disorders. Various phytocompounds including pongamol, purpurin, purpurenone, tephrosin, bulnesol, tephrostachin, β‐sitosterol, and so on have been reported. Modern pharmacological studies have shown that the plant have wound healing, antileishmanial, anticarcinogenic, antimicrobial, antioxidant, hepatoprotective, antifertility, antispermatogenic, anti‐diarrheal, diuretic, and insecticidal properties. Acetylcholinesterase inhibitory action reported from this plant aids its utilization for the development of drugs for Alzheimer's and dementia neurological disorders. Among the known active compounds of T. purpurea, tephrostachin is responsible for antiplasmodial activity, tephrosin, pongaglabol, and semiglabrin exerts antiulcer activity while quercetin, rutin, β‐sitosterol, and lupeol are mainly responsible for its anti‐inflammatory and anti‐cancer properties. From different toxicological studies, concentrations up to 2, 000 mg/kg were considered safe. The present review comprehensively summarizes the ethnomedicine, phytochemistry, pharmacology, and toxicology of T. purpurea . Further research on elucidation of the structure–function relationship among active compounds, understanding of multi‐target network pharmacology and clinical applications will intensify its therapeutic potential.